Sustainable mining in Northern Finland : standardization and current practices - Salonen, Anniina (2020)
This thesis examines sustainable mining state and initiatives in metal mining company. The goal of the study was to evaluate current performance against Finnish TSM -standard (Towards Sustainable Mining –standard) with gap analysis and create a goal-directed step to milestone –project plan in order to develop the standard in Boliden Kevitsa. The goal was also recognize how Finnish TSM standard could be combined with the most commonly used ISO management standards ISO14001, ISO45001 and ISO50001. Study was per-formed as a qualitative single case study for Boliden Kevitsa Mining Oy. As a result of study it was noticed that the Finnish TSM standard can be combined the easiest with the ISO14001 standard consistent environmental management system but also with ISO45001 standard consistent health and safety management system as well as ISO50001 standard consistent energy management system. As a result is was also noticed that significant gaps in case organization were concerning the stakeholder cooperation activities in the facility level operation. Tässä diplomityössä tutkittiin kestävän kaivostoiminnan työkaluja ja tilaa metallimalmikai-voksella. Työn tavoitteena oli arvioida nykyistä toiminnan tilaa kaivosvastuujärjestelmää vasten gap –analyysin avulla ja laatia tavoitteellinen projektisuunnitelma suomalaisen kai-vosvastuujärjestelmän kehittämiselle kaivosyhtiössä. Tavoitteena oli myös tunnistaa, kuinka kaivosvastuujärjestelmä voidaan yhdistää yleisimmin käytettyihin ISO johtamisjärjestelmäs-tandardeihin ISO14001, ISO45001 ja ISO50001. Työ tehtiin laadullisena tapaustutkimuk-sena Boliden Kevitsa Mining Oy:lle. Työn tuloksena havaittiin, että kaivosvastuujärjestelmä voidaan implementoida parhaiten ISO14001 standardin mukaiseen ympäristöjohtamisjärjes-telmään, mutta myös ISO45001 mukaiseen työterveys- ja turvallisuusjohtamisjärjestelmään sekä ISO50001 mukaiseen energianhallintajärjestelmään. Tuloksena havaittiin myös suu-rimpien kohdeyrityksen puutteiden gap analyysissä kohdistuvan sidosryhmäyhteistyöhön ...